Influence of microleakage, surface roughness and biofilm control on secondary caries formation around composite resin restorations: an in situ evaluation (Journal of Applied Oral Science, 2009)
This study was carried out to evaluate in situ the influence of microleakage, surface roughness and biofilm control on caries formation around composite resin restorations. During 28 days, 12 volunteers wore palatal devices containing bovine enamel slabs restored with composite resin. Restorations were made without leakage, when the adhesive system was applied, or with leakage, when adhesive system was omitted. Half of the restorations in each group were finished and the remaining were finished and polished. In one side of the palatal device, biofilm was left to accumulate over the restored slabs, and in the other side dental slabs were brushed, to allow biofilm removal. There was an extraoral application of 20% sucrose solution (8x/day) over the enamel slabs. The formation of caries lesions (white spots) was evaluated by visual inspection under stereomicroscopy. Additionally, the dental slabs were sectioned and observed under polarized light microscopy. Data were submitted to Kruskal-Wallis test and Spearman's correlation test at 5% significance level. Polishing and bonding were not significant factors regarding white spot formation (p>;0.05). Biofilm control (brushing) was associated with reduction of caries formation close to the restorations (p